Optimizing raffinose family oligosaccharides content in plants: A tightrope walk - Sanyal, Rajarshi; Kumar, Sandeep; Pattanayak, Arunava; Kar, Abhijit; Bishi, Sujit K. (Frontiers in Plant Science, 2023)
Plants synthesize various compounds for their growth, metabolism, and stress mitigation, and one such group of compounds is the raffinose family of oligosaccharides (RFOs). RFOs are non-reducing oligosaccharides having galactose residues attached to a sucrose moiety. They act as carbohydrate reserves in plants, assisting in seed germination, desiccation tolerance, and biotic/abiotic stress tolerance. Although legumes are among the richest sources of dietary proteins, the direct consumption of legumes is hindered by an excess of RFOs in the edible parts of the plant, which causes flatulence in humans and monogastric animals. These opposing characteristics make RFOs manipulation a complicated tradeoff. An in-depth knowledge of the chemical composition, distribution pattern, tissue mobilization, and metabolism is required to optimize the levels of RFOs. The most recent developments in our understanding of RFOs distribution, physiological function, genetic regulation of their biosynthesis, transport, and degradation in food crops have been covered in this review. Additionally, we have suggested a few strategies that can sustainably reduce RFOs in order to solve the flatulence issue in animals. The comprehensive information in this review can be a tool for researchers to precisely control the level of RFOs in crops and create low antinutrient, nutritious food with wider consumer acceptability.